Vacancy formation enthalpies of high-entropy FeCoCrNi alloy via first-principles calculations and possible implications to its superior radiation tolerance. Issue 2 (February 2018) - Chen, Weiliang; Ding, Xueyong; Feng, Yuchao; Liu, Xiongjun; Liu, Kui; Lu, Z.P.; Li, Dianzhong; Li, Yiyi; Liu, C.T.; Chen, Xing-Qiu
Abstract: Because atoms in high-entropy alloys (HEAs) coordinate in very different and distorted local environments in the lattice sites, even for the same type of constituent, their point defects could highly vary. Therefore, theoretical determination of the thermodynamic quantities (i.e., defect formation enthalpies) of various point defects is rather challenging because each corresponding thermodynamic quantity of all involve constituents is not unique. The knowledge of these thermodynamic quantities is prerequisite for designing novel HEAs and understanding the mechanical and physical behaviors of HEAs. However, to date there has not been a good method to theoretically derive the defect formation enthalpies of HEAs. Here, using first-principles calculations within the density functional theory (DFT) in combination of special quasi-random structure models (SQSs), we have developed a general method to derive corresponding formation enthalpies of point defects in HEAs, using vacancy formation enthalpies of a four-component equiatomic fcc-type FeCoCrNi HEA as prototypical and benchmark examples. In difference from traditional ordered alloys, the vacancy formation enthalpies of FeCoCrNi HEA vary in a highly wide range from 0.72 to 2.89 eV for Fe, 0.88–2.90 eV for Co, 0.78–3.09 eV for Cr, and 0.91–2.95 eV for Ni due to high-level site-to-site lattice distortions and compositional complexities. On average, the vacancy formation enthalpies of 1.58 eV for Fe, 1.61 eV for Cr, 1.70 eV for Co and 1.89 eV for Ni are all larger than that (1.41 eV) of pure fcc nickel. This fact implies that the vacancies are much more difficult to be created than in nickel, indicating a reasonable agreement with the recent experimental observation that FeCoCrNi exhibits two orders of amplitudes enhancement of radiation tolerance with the suppression of void formation at elevated temperatures than in pure nickel.